Green Halal Supply Chain in Malaysian Halal Food Companies: A Conceptual Framework - Abdullah, Rohani; Sabar, Rohafiz; Mustafar, Mastora (International Journal of Supply Chain Management, 2018)
The aim of becoming a global Halal hub has been outlined in the Third Industrial Master Plan 2006–2020 (IMP3) and Malaysia now is on target to attain the status by 2020. However, the progression needs to be geared with a holistic ecosystem that enable closing compliance loop within Halal supply chain. Thus, calling for sustainable development to strengthen the Halal definition. Despite the urge, the degree of readiness to employ green practices in Halal food industry is still vague and the issues are still new and developing. Food industry is one of the major contributors to environmental problems, large amount of waste is generated from food industry, by promoting sustainability in producing Halal food can reduce their environmental footprint and will benefit Malaysia where other countries can recognize Malaysian Halal standards not only for hygiene and safety but also as a symbol of eco-friendly practices. Therefore, green Halal supply chain is now seen to be central towards global Halal hub. Responding to these needs, this study is expected; (1) to identify what are the green practices implemented in collaboration with supplier and customer in managing Halal food supply chain (2) to assess what is sustainable performance achieved from green practices implemented (3) to determine if supplier-customer collaboration moderates the impact of green practices on sustainable performance. This study will employ mixed methods of qualitative and quantitative to answer the study’s objectives. Overall, this study is expected to present a model that provides a comprehensive view on Green Halal supply chain concerning supplier-customer collaboration in green practices. The model can help the industry and policy maker to identify what green practices are feasible to collaborate with and what are the related benefits and barriers. Engaging Green Halal Supply Chain can further improve Malaysian reputation as the world’s leading Halal hub.